Geliat Penafsiran Kontemporer: Kajian Multi Pendekatan - Siti Fahimah (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2021)
The Qur'an is a text that will not be able to speak unless it is spoken by someone, speaking of that text is called interpretation, it will continue to develop along with the development of the conditions of the times and also the times, because the text of the Qur'an will never change at any time, but what changes is the interpretation. This is where the stretch of interpretation always develops according to changing contexts, especially the development of interpretation in the modern era, there are many approaches that can be offered to interpret the Qur'an even though it is only thematic and not the entire contents of the Qur'an. In this study, the focus of the discussion is the method used by contemporary figures, nowadays which is often used by contemporary interpreters is to use the thematic method using hermeneutic, semiotic, semantic, maqasidi and meaning cum maghza approaches. These approaches are likely to be developed again as the scientific development of the current and future generations of the Qur'an. This study uses a descriptive method, namely by presenting various interpretive approaches that emerged then and now.